Alcohol Consumption, Left Atrial Diameter, and Atrial Fibrillation. Issue 9 (14th September 2016) - McManus, David D.; Yin, Xiaoyan; Gladstone, Rachel; Vittinghoff, Eric; Vasan, Ramachandran S.; Larson, Martin G.; Benjamin, Emelia J.; Marcus, Gregory M.
Abstract : Background: Alcohol consumption has been associated with atrial fibrillation (AF) in several epidemiologic studies, but the underlying mechanisms remain unknown. We sought to test the hypothesis that an atrial myopathy, manifested by echocardiographic left atrial enlargement, explains the association between chronic alcohol use and AF. Methods and Results: We evaluated the relationship between cumulative alcohol consumption and risk of incident AF in 5220 Offspring and Original Framingham Heart Study participants (mean age 56.3 years, 54% women) with echocardiographic left atrial size measurements. The incidence of AF was 8.4 per 1000 person‐years, with 1088 incident AF cases occurring over a median 6.0 years (25th–75th percentiles 4.0–8.7 years) of follow‐up. After multivariable adjustment for potential confounders, every additional 10 g of alcohol per day (just under 1 drink per day) was associated with a 0.16 mm (95% CI, 0.10–0.21 mm) larger left atrial dimension. Also in multivariable adjusted analysis, every 10 g per day of alcohol consumed was associated with a 5% higher risk of developing new‐onset AF (hazard ratio, 1.05; 95% CI, 1.01–1.09). An estimated 24% (95% CI, 8–75) of the association between alcohol and AF risk was explained by left atrial enlargement. Conclusions: Our study of a large, community‐based sample identified alcohol consumption as a predictor of left atrial enlargement and subsequent incident AF. Left atrial enlargement may be an intermediate phenotype along the causal pathway linking long‐term alcohol consumption to AF.